Spatial market integration analysis of plantain markets in mid Ghana - Christina Antwiago Amarchey; Paul Adjei Kwakwa (Cogent Business & Management, 2024)
AbstractThe paper estimates the degree of integration of plantain prices in three selected markets to assess the efficiency of the plantain marketing system in mid Ghana. The selected markets are Techiman in Bono East Region, Kenyasi and Duayaw Nkwanta markets both in Ahafo Region of Ghana. The spatial market integration analysis was done using the error correction model on monthly wholesale real prices in Ghana cedis (GH¢) per 9–11 kg bunch of plantain from 2006 to 2015. The findings of the analysis indicate that the plantain markets are weakly integrated spatially with an overall degree of integration of 17 percent which suggests weak market efficiency. Therefore, strengthening the implementation of government policy on market information, especially in producing areas, will be useful in improving plantain market efficiency.